Penerapan Single Exponential Smoothing Dalam peramalan Kesempatan Kerja Terhadap Pencari Kerja Terdaftar - Patmawati Patmawati; Iqbal Kamil Siregar; Akmal Akmal (Forum Kerjasama Pendidikan Tinggi, 2022)
The Tanjungbalai City Manpower Office was established with the aim of being a mediator between companies or job seekers in terms of the fulfillment of manpower needs and job vacancies that enter every year. The problems faced in Tanjungbalai City certainly cannot be separated from job seekers who have not found jobs according to their talents, interests and experiences. This is partly due to the last education level which is still not evenly distributed and there are no companies that match the criteria for the latest education of these job seekers. The purpose of the study is to find out the general description of Job Opportunities for Registered Job Seekers at the Tanjungbalai City Manpower Office, to find out the Single Exponential Smoothing method model that is applied to the system can be used by the Tanjungbalai City Manpower Office in order to reduce the limitations of Job Opportunities for Registered Job Seekers with the Single method. Exponential Smoothing, knowing the MAPE value of the Single Exponential Smoothing method for forecasting Job Opportunities for Registered Job Seekers at the Tanjungbalai City Manpower Office in 2022 using the Single Exponential Smoothing method